Utilization of Islamic Banking and Tiktok Shop for Micro, Small, and Medium Enterprises (UMKM) in East Jakarta - Siregar, Muhammad Edo Suryawan; Susita, Dewi; Suherman; Kurnianti, Destria; Rahmi; Wibowo, Setyo Ferry; Dalimunthe, Sholatia; Mahfirah, Titis Fatarina; Malzara, Vidia Ratu Balqis; Zahro, Khalisatuz; Sari, Rini Nurmala (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
MSME empowerment needs to be done to improve MSME’s welfare. This community service team intends to provide training for MSME so they can improve their product and income. The target of this empowerment is MSMEs around the East Jakarta Industry, Trade, Small and Medium Enterprises Cooperative Office in Cakung District, East Jakarta. The training material is presented in the form of material presentation by resource persons followed by discussion. This community service activity proved to be able to provide an understanding of Islamic banking and product.